Reoperace plastik LCA v našem souboru - Hanus, M; Stančák, A; Šťastný, E; Trč, T (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2021)
INTRODUCTION The authors present the long-term clinical outcomes of revision anterior cruciate ligament (ACL) reconstruction. The aim was to compare the surgical technique with respect to the clinical outcomes within 3 years postoperatively. MATERIAL AND METHODS The clinical evaluation of revision anterior cruciate ligament reconstructions performed at our department in 2002-2017 was carried out. A total of 82 patients were included in the study, male as well as female patients. Apart from the clinical outcomes, the associated procedures performed as a consequence of other injuries or damage to other intraarticular structures, the surgical technique as such, potential complications of revision reconstruction and causes of failure were studied. The same criteria were followed up in all the patients - clinical range of motion (ROM) of the operated knee, knee stability - pivot shift test, instrumental Lachman test using Rolimeter, IKDC subjective form, Tegner and Lysholm scores. RESULTS In the group of patients, the surgical technique involved the use of a harmstring tendon autograft as a new graft for revision in 43 patients, a BTB autograft in 25 patients, and a BTB cadaverous graft in 14 patients. In 24 cases, a two-stage surgery was performed. The interval between the first- and the second-stage procedure ranged from 6 weeks up to 6 months, with the median of 62.4 days. During the evaluation, no difference was observed whether one-stage or two-stage surgery was performed, therefore this is not reflected in the overall evaluation. The clinical evaluation resulted in the following mean values when comparing the preoperative and final postoperative findings: The mean value of the IKDC subjective knee form score was 42 (30-62) preoperatively and increased to 77 (66-89) at 3 months. The values obtained at 6 months, 1 year and 3 years were 84 (73-93), 88 (79-100) and 89 (78-100), respectively. The mean value of the Lysholm score in the followedup study population was 63 preoperatively, which indicates a clearly poor result. The score rose to 71 (62-88) at 3 months, to 79 (67-92) at 6 months, to 89 (67-94) at 1 year, and at 3 years the mean score was again 89 (66-95). No serious complications were reported. CONCLUSIONS The results confirmed sufficient postoperative stability of the knee joint. In terms of function and pain perception the treatment was considered appropriate. No major complications occurred during surgeries. Based on the results, the authors foresee the patient s return to sports, at least at recreational level. Key words: anterior cruciate ligament, reconstruction, revision reconstruction, knee arthroscopy, instrumentarium.
Keywords: Tendons; poranění předního zkříženého vazu; Anterior Cruciate Ligament Reconstruction; Humans; Knee Joint; lidé; Anterior Cruciate Ligament; Female; mužské pohlaví; ligamentum cruciatum anterius; Anterior Cruciate Ligament Injuries; Male; kolenní kloub; Treatment Outcome; výsledek terapie; ženské pohlaví; rekonstrukce předního zkříženého vazu; šlachy